The Impact of District Assembly Common Fund on Socio-Economic Activities in the New Juaben Municipality - Bismark Okrah; Ronald Osei Mensah; Charles Quansah (Mediterranean Journal of Social Sciences, 2023)
This paper's value is in determining how the district assembly common money affects socioeconomic activity in NJM. The study, which focused on five thematic areas—instruction, health, poverty eradication, social facilities, and infrastructural development—obtained quantitative and qualitative data using questionnaires, interview guides, and observation. The sample size was thirty-two (32) and included every member of the NJM Assembly. According to the report, society has benefited from a number of advancements in the areas of health care delivery, poverty reduction, social amenities, and infrastructure development. Researchers suggest, based on their findings, that a program be funded by DACF with the goal of cooperating with the Ministry of Food and Agriculture to create a rural environment that is conducive to agricultural development. Last but not least, the management of the fund should be governed by tight rules. The impoverished should be the objective, not the wealthy. Received: 11 December 2022 / Accepted: 21 February 2023 / Published: 6 March 2023